Association Between Community-Based Total Sanitation (CLTS) Pillars and Diarrhea Incidence in Wetland Communities of South Indralaya - Trisnaini, Inoy; Pratiningsih, Widya Ayu; Putri, Dini Arista; Juniarni, Annisa; Febriana, Dwita; Safana, Hanifaus; Firdaus, Amirarosa (Poltekkes Kemenkes Surabaya, 2025)
Diarrhea remains a major global health problem and a leading cause of mortality among children under five, often exacerbated by inadequate sanitation and limited access to clean water. Community-Led Total Sanitation (CLTS) represents a national strategy for preventing environment-based diseases, including diarrhea. However, researchers have not comprehensively studied the effectiveness of each CLTS pillar within specific geographical contexts, such as wetland areas. This study aims to identify the relationship between sanitation factors of Community-Led Total Sanitation (CLTS) pillars and diarrhea incidence in the South Indralaya wetland community. This quantitative research employed a cross-sectional design and selected 100 respondents using a purposive sampling technique. Data were collected through questionnaires and analyzed using chi-square test for bivariate analysis and logistic regression for multivariate analysis. Our results indicated a diarrhea prevalence of 45% among total respondents. Multivariate analysis revealed that two CLTS pillars significantly associated with diarrhea incidence. Pillar 1, concerning latrine availability, showed that households without latrines had a 3.4 times higher risk of experiencing diarrhea (OR = 3.400; 95% CI: 1.037–11.155). Pillar 4, regarding unsafe waste management, also served as a strong predictor, increasing diarrhea likelihood up to 3.296 times (P-value = 0.008; Exp(B) = 3.296; 95% CI: 1.359–7.996). We found that latrine type (P = 0.053) acted as a confounder, which influenced the risk estimation of the main variables in the model. This study concludes that CLTS pillars 1 and 4, related to feces and solid waste management, are key determinants of diarrhea incidence in South Indralaya. Interventions focusing on improving access to and quality of latrines, as well as safe waste management practices, are crucial for reducing diarrhea incidence in the region.